DRIVING TRANSFORMATION FROM THE TOP: DISTELL’S JOURNEY TO END-TO-END SUPPLY CHAIN EXCELLENCE - Petrarolo, Dino; Everson, Cecil (The South African Journal of Industrial Engineering, 2019)
Distell Group (a listed South African alcoholic beverage company) embarked on a business improvement journey that required a significant change to its supply chain structure and capability, which were inadequate to meet its 2020 strategic ambitions, to improve its performance levels. In partnership with Competitive Capabilities International (CCi), Distell developed and executed an end-to-end supply chain and excellence strategy to transform this function. This paper describes how this strategy, through four key strategic levers, effectively transformed its supply chain function as well as the resultant performance benefits that ensued, primarily in its South African operations.